Post-marketing surveillance study of the long-term use of mizoribine for the treatment of lupus nephritis: 2-Year results. Issue 1 (2nd January 2018) - Takeuchi, Tsutomu; Okada, Kenya; Yoshida, Hisao; Yagi, Nobuyuki
Abstract: Objectives: To understand the status of mizoribine use in patients with lupus nephritis (LN) and to collect safety- and efficacy-related data on 2-year treatment with mizoribine. Methods: A continuous survey was conducted between March 2010 and July 2015. Results: The analysis set included 559 patients (mean age 39.5 years, females 82.6%, mean duration of systemic lupus erythematosus (SLE) 8.4 years, mean duration of LN 5.9 years). Renal function was satisfactory for 6 months, but worsened from 12 months, with significant worsening at 24 months. By the ACR 2006 remission criteria (eGFR >60), at 24 months, 26.5% of patients achieved complete remission, and 63.3% achieved complete or partial remission. The urine protein to creatinine ratio decreased significantly. The SLE Disease Activity Index 2000 score decreased significantly at 12 and 24 months. Overall, 98 (17.5%) patients experienced 124 adverse drug reactions (ADRs); 3.6% experienced serious ADRs. Mizoribine was used with a steroid in 99.3% and an immunosuppressant in 51.2%; tacrolimus was used in 43.8%. The oral steroid dosage decreased from baseline to 24 months. The incidence of ADRs was not significantly different with concomitant tacrolimus use. Conclusions: The results suggest that long-term mizoribine is safe and effective, even when used with tacrolimus.